Republic of Madagascar : Poverty Reduction Strategy Paper; Annual Progress Report for 2007 and First Semester of 2008. (IMF Staff Country Reports; Country Report, 2009)
The report examines the annual report of Madagascar's Poverty Reduction Strategy Paper. Madagascar's economic situation has been characterized by steady growth estimated at 5.0 percent on average against an average annual demographic growth rate of 2.8 percent. However, the living standard of the population as captured by the indicators related to the big objectives of the Madagascar Action Plan has not kept up with this pace. The organic law on public finances and the new code of public procurements have become more effective.